Differences in the Effectiveness of Hypnocircumcision and Free Needle Anesthesia on Children's Pain Levels During the Circumcision Process - Heri Saputro; Muhamad As'ad Efendy (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study aimed to compare the level of pain in children during the circumcision process between the hypnosis method and free needle anesthesia (anesthesia without a needle). In the implementation of this study, the respondents (children) were divided into two groups, namely the group of children who were hypnotized and the group of children who used free needle anesthesia (anesthesia without a needle). researchers ranging from children aged 7-15 years), after which the data will be analyzed and concluded. The results of this study indicate that there are differences in pain levels with the hypnosis method and the neddle injection method with a sig value of 0.00 < 0.05 (Mann-Whitney U test). From the results of this study it was also found that hypnosis was more effective in overcoming pain in children during the circumcision process. It can be concluded that hypnosis is more effective than free needle injection.